The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1002/pros.24173
|View full text |Cite
|
Sign up to set email alerts
|

The role of lymph node dissection in salvage radical prostatectomy for patients with radiation recurrent prostate cancer

Abstract: Purpose: To examine the effect of lymph node dissection on the outcomes of patients who underwent salvage radical prostatectomy (SRP). Material and Methods:We retrospectively reviewed data from radiation-recurrent patients with prostate cancer (PCa) who underwent SRP from 2000-2016. None of the patients had clinical lymph node involvement before SRP. The effect of the number of removed lymph nodes (RLNs) and the number of positive lymph nodes (PLNs) on biochemical recurrence (BCR)-free survival, metastases fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…29 Notably, we found that with a pT3 disease prevalence of 38% the NPV was strong (92%), which allow considering PSMA-PET/CT as a rule-out test for the nonorgan confined disease in patients with radiorecurrent PCa. Considering detection rates of local recurrence-96% for MRI and 100% for PSMA-PET/CT, both imaging modalities are reliable tools in this setting, which has been also shown previously by Liu et al 30 Our study shows that due to 100% specificity and 100% PPV patients with positive lymph nodes on PSMA-PET/CT should either undergo extended PLND, which may improve survival outcomes, 16 or can forgo SRP due to significant morbidity and lower chance of cure and may be considered for other treatment modalities such as systemic therapy. 7,20 A recent multicenter prospective phase 3 trial 31 reported PSMA-PET sensitivity of 40% and specificity of 95% for lymph node metastases at primary RP.…”
Section: Patient Characteristicssupporting
confidence: 82%
See 3 more Smart Citations
“…29 Notably, we found that with a pT3 disease prevalence of 38% the NPV was strong (92%), which allow considering PSMA-PET/CT as a rule-out test for the nonorgan confined disease in patients with radiorecurrent PCa. Considering detection rates of local recurrence-96% for MRI and 100% for PSMA-PET/CT, both imaging modalities are reliable tools in this setting, which has been also shown previously by Liu et al 30 Our study shows that due to 100% specificity and 100% PPV patients with positive lymph nodes on PSMA-PET/CT should either undergo extended PLND, which may improve survival outcomes, 16 or can forgo SRP due to significant morbidity and lower chance of cure and may be considered for other treatment modalities such as systemic therapy. 7,20 A recent multicenter prospective phase 3 trial 31 reported PSMA-PET sensitivity of 40% and specificity of 95% for lymph node metastases at primary RP.…”
Section: Patient Characteristicssupporting
confidence: 82%
“…Our study shows that due to 100% specificity and 100% PPV patients with positive lymph nodes on PSMA‐PET/CT should either undergo extended PLND, which may improve survival outcomes, 16 or can forgo SRP due to significant morbidity and lower chance of cure and may be considered for other treatment modalities such as systemic therapy 7,20 . A recent multicenter prospective phase 3 trial 31 reported PSMA‐PET sensitivity of 40% and specificity of 95% for lymph node metastases at primary RP.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Furthermore, those who did undergo PLND were noted to have increased CSS, with the lymph node count showing a direct correlation with increasing CSS up to seven nodes [51]. In a separate retrospective multicenter cohort, pathologic nodal involvement was found to be associated with an increased risk of BCR, the development of metastasis, and decreased OS among patients undergoing salvage RP for radio-recurrent prostate cancer [52]. Given these prognostic and potential therapeutic benefits, performing PLND at the time of salvage RP should be standard of practice when possible.…”
Section: The Role Of Lymph Node Dissection and Seminal Vesicle Biopsymentioning
confidence: 90%